Feasibility of using Mediterranean rainfed crops in poultry rations - Farran M.T.; Yau S.K.; Daghir N.J.; Barbour G.W.; Usayran N.N. (Economics of drought and drought preparedness in a climate change context, 2010)
Large fluctuation in market price and availability of conventional poultry feed ingredients in the Mediterranean region is caused by the global shift towards the production of bio-fuel and further exacerbated by the reduced water availability caused by climatic changes especially in southern Mediterranean countries. Poultry researchers in the region are urged to consider domestic rainfed crops as alternatives to corn and soybean meal. In line with this strategy, this paper summarizes the work conducted at the American University of Beirut in the fields of agronomy and poultry nutrition on barley, vetch and safflower and presents the economic feasibility of using such rainfed crops. A recent yield survey in different locations in Lebanon and in rainy years or with necessary supplementary irrigation in years with irregular rainfall distribution, showed that barley, vetch, safflower and wheat produce 3.8, 3.2, 3.3 and 4.9 t/hectare, respectively. Properly detoxified vetch could be incorporated in broiler and layer rations at 60 percent. In broiler diets, barley could be used at 25 percent with enzyme supplementation whereas safflower meal substituted 75 percent of soybean meal in diets supplemented with lysine and methionine. An economic feasibility study showed that only local barley and safflower meal could be incorporated in practical least cost rations. Moreover, safflower increases the production value by US$ 70/hectare over non-subsidized wheat.
2. International Conference on Drought Management, 2010/03/04-06, Istanbul (Turkey)